PENDAMPINGAN PENGOLAHAN LIMBAH KANDANG MENJADI PUPUK ORGANIK DI DESA PERSIAPAN BATU ASAK - Sukarne, Sukarne; Sutaryono, Yusuf Akhyar; Harjono, Harjono; Maslami, Vebera; Hakim, Yusufi Ahmad Fathul (Jurnal Abdi Insani, 2025)
The livestock sector has long been recognized by the community and remains acrucial economic pillar for family livelihoods. Through the application of simpletechnology, livestock waste such as manure, urine, and leftover feed can beprocessed into organic fertilizer, which enriches the soil, enhances agriculturalproductivity, and reduces dependence on costly inorganic fertilizers. Theseskills have the potential to improve productivity and sustainability in agriculturein the village of Desa Persiapan Batu Asak, Praya Barat District, Lombok Tengah.Based on this perspective, a training program on processing livestock waste intoorganic fertilizer was implemented to improve the welfare of farmers andlivestock breeders in Desa Persiapan Batu Asak, Praya Barat District, LombokTengah. The method of implementing the training activities for making organicfertilizer is carried out in two stages, namely; the first stage is providing trainingmaterials with lectures and discussions and distributing brochures so thatparticipants can understand the steps and techniques for making organicfertilizer. The second stage is carried out by means of direct demonstrationpractices so that livestock farmers can do it properly and correctly. The positiveimpact of this training is that livestock farmers can have skills in processingmanure waste into organic fertilizer. In addition, the organic fertilizer producedcan be used as agricultural plant fertilizer and can reduce the use of inorganicfertilizers which are increasingly rare and expensive. Organic fertilizer also hasbenefits in improving soil conditions physically, chemically, and biologically sothat the land in the Village of Preparation of Batu Asak is always maintained inits fertility.